Caracterização do cordão de solda de 410 NiMo utilizando o processo de soldagem TIG - Pitoli, Ana Carolina Goulart (2016)
The turbine blades used in hydroelectric plants suffer from erosion and the consequent appearance of cracks. These blades need repairs in order to guarantee the safety and efficiency of its work. Such repairs can be done using the process of material deposition by welding procedure. The present work studies the parameters of the TIG welding process with rod feeding for the execution of the repair procedure. The samples were obtained from a turbine blade made of soft martensitic stainless steel CA6NM, and welded adding ER410NiMo electrode. The objective is to evaluate the weld quality through the liquid penetrant test, and also estimate the parameters on the weld bead hardness and on the Heat-affected zone (HAZ), plus the verification of the presence of ferrite in the microstructure.